2016
DOI: 10.1002/2016jd025028
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of bacterial aerosols in response to synoptic weather and land‐sea breeze at a seaside site downwind of the Asian continent

Abstract: Airborne bacteria are a major group of bioaerosols, but their temporal and spatial variations in the atmosphere are poorly understood due to a lack of accurate information at an appropriate temporal resolution. In this study, we quantified the concentration and viability of airborne bacteria at a seaside site on the southwestern coast of Japan in spring to investigate their association with synoptic weather, which was governed alternately by cyclones and anticyclones moving in the middle‐latitude westerly flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…In general, the concentration of airborne bacteria over diverse marine areas is on the order of 10 4 –10 5 cells m −3 , which is lower by a factor of 10–100 than those (10 5 –10 7 cells m −3 ) at inland and coastal sites (Bowers, McLetchie, et al, ; Bowers, Sullivan, et al, ; Chi & Li, ; Hara & Zhang, ; Murata & Zhang, , ). Previous measurements have also shown that the bacterial concentrations over the sea could be lower by a factor of up to 100–1,000 than those in continental air (Prospero et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the concentration of airborne bacteria over diverse marine areas is on the order of 10 4 –10 5 cells m −3 , which is lower by a factor of 10–100 than those (10 5 –10 7 cells m −3 ) at inland and coastal sites (Bowers, McLetchie, et al, ; Bowers, Sullivan, et al, ; Chi & Li, ; Hara & Zhang, ; Murata & Zhang, , ). Previous measurements have also shown that the bacterial concentrations over the sea could be lower by a factor of up to 100–1,000 than those in continental air (Prospero et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A large proportion (60–88% on average, up to 100%) of the bacteria in airborne aerosols or included in cloud water and precipitation are viable (with intact cell membranes) or metabolically active (Bauer et al, ; DeLeon‐Rodriguez et al, ; Hill et al, ; Hu, Murata, Toyonaga, et al, ; Murata & Zhang, , ; Stopelli et al, ). Previous studies have found that bacteria in cloud water can actively grow, reproduce, and metabolically degrade organic substances, and the viability or metabolic activities of airborne bacteria interact with atmospheric chemical and physical processes (Ariya & Amyot, ; Deguillaume et al, , and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Dust arrival always coincided with elevated levels of viable and non-viable bacteria, in which the increase of non-viable bacteria was more remarkable than that of viable bacteria. In later observations at the same areas, it was found that locally-originating bacteria were predominated by viable bacteria (Murata and Zhang 2016). Therefore, the remarkable increase of non-viable bacterial cells during dust events was definitely caused by bacteria brought by dust, although the amounts of bacteria adhering to dust particles and freely-floating bacteria in dust plumes have not yet been accurately quantified.…”
Section: Transport With Asian Dustmentioning
confidence: 94%
“…Data were from Zhang (2014, 2016) overturn of surface temperature difference between land and sea water in the daytime and the nighttime. The increase is considered to be the consequence of the outbreak of bacterial cells which had accumulated in the nearsurface air from water surface in the early morning and land surface in the late afternoon when the surface air was neutral to stable (Murata and Zhang 2016).…”
Section: Response To Weather Changes On Synoptic and Local Scalesmentioning
confidence: 99%
“…In Japan, airborne microbial abundances increase in response to atmospheric depressions, which travel from the Asian continent (Murata and Zhang, 2016).…”
Section: Introductionmentioning
confidence: 99%